2017
DOI: 10.1111/bdi.12470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cognitive reserve on neuropsychological functioning in bipolar disorder: Findings from a 5‐year longitudinal study

Abstract: This study has explored the influence of cognitive reserve on preservation of specific cognitive abilities over time in BP. The BP group did not demonstrate accelerated cognitive decline over 5 years compared to the HC group. Although the trajectory of cognitive change over time was similar between BP patients and HCs, higher overall intellectual ability may be a protective factor against cognitive decline, particularly for BP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 51 publications
(95 reference statements)
4
28
0
Order By: Relevance
“…As a result, researchers have begun to look for risk and protective factors among lifestyle or demographic features which may differ between participants. These features include premorbid intelligence quotient (23), sleep disturbances (24), and more recently, variables related to cognitive reserve, such as education levels (25)(26)(27). A quantitative synthesis of these studies using methods such as meta-regression may provide important information for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, researchers have begun to look for risk and protective factors among lifestyle or demographic features which may differ between participants. These features include premorbid intelligence quotient (23), sleep disturbances (24), and more recently, variables related to cognitive reserve, such as education levels (25)(26)(27). A quantitative synthesis of these studies using methods such as meta-regression may provide important information for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large-sample studies in BD have reported that higher cognitive reserve is associated with better psychosocial functioning and cognitive performance with respect to processing speed, working memory, verbal and visual memory, and executive function. 10,11 In the present sample, the mean years of education were 11.3 + 4.1 and 9.9 + 4.1 for EOBD and LOBD, respectively. The lengths of education in our participants were similar to those of other Taiwanese samples, 2,5 although relatively shorter than those reported in Western BD populations.…”
Section: Discussionmentioning
confidence: 57%
“…Lewandowski et al,6 indicating particular impairments of information processing speed in aged people with BD. Recently, large-sample studies in BD have reported that higher cognitive reserve is associated with better psychosocial functioning and cognitive performance with respect to processing speed, working memory, verbal and visual memory, and executive function 10,11. Recently, large-sample studies in BD have reported that higher cognitive reserve is associated with better psychosocial functioning and cognitive performance with respect to processing speed, working memory, verbal and visual memory, and executive function 10,11.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a naturalistic study, Hinrichs et al 1 examined cognitive functioning across 5 years in 159 subjects with bipolar disorder and 54 healthy controls. They found that, in bipolar subjects, higher baseline intellectual ability was associated with greater 5-year cognitive stability; and lower verbal intelligence quotient (IQ) and education were associated with greater cognitive decline in specific domains.…”
Section: Dear Editorsmentioning
confidence: 99%